Search for tick-borne pathogens in the Svalbard archipelago and Jan Mayen - Elsterová, J. (Jana); Černý, J. (Jiří); Müllerová, J. (Jana); Šíma, R. (Radek); Coulson, S.J.; Lorentzen, E.; Strøm, H.; Grubhoffer, L. (Libor) (Polar Research, 2015)
The tick species Ixodes uriae, parasitizing seabirds in the Arctic, may transmit many pathogens including various arboviruses, Borrelia spirochetes and Babesia apicomplexans. These pathogens may pose an important additional stress to seabirds, which are already stressed by environmental changes such as pollutants and decreased food availability. Here, we present the results of the first screening for arboviruses of the genera Flavivirus, Alphavirus, Orthobunyavirus, Phlebovirus and Orbivirus, as well as Borrelia spirochetes and Babesia apicomplexans from Svalbard and Jan Mayen. Using polymerase chain reaction technology with genus-specific primers, we tested 89 ticks collected on Jan Mayen, Bjornoya and Spitsbergen between 2008 and 2012. We did not detect any of the screened tick-borne pathogens. Nevertheless, these pathogens may be introduced to Svalbard and Jan Mayen by migratory birds in the near future. The increasing numbers of ticks appearing in the studied areas make this introduction even more likely. Such an introduction would have serious impact on seabird ecology as well as on human public health. Therefore, continuous careful surveillance and monitoring of possible tick-borne pathogen introductions is important.